Breaking new ground: first report of integrating clinical, hematobiochemical, sonographic, and pathological findings in dromedary camels (Camelus dromedarius) with hepatic fibrosis - Mohamed Tharwat; Hazem M. M. Elmoghazy; Hazem M. M. Elmoghazy; Mohie Haridy (Frontiers in Veterinary Science)
IntroductionHepatic fibrosis is a progressive liver disorder that can lead to significant morbidity in animals, yet its characteristics remain poorly described in dromedary camels (Camelus dromedarius). This study aims to provide a comprehensive characterization of the clinical, hematobiochemical, ultrasonographic, and histopathological features associated with hepatic fibrosis in dromedaries.MethodsSixteen female camels presenting with clinical signs of inappetence, weight loss, and discolored urine were evaluated and compared with eleven clinically healthy controls. All animals underwent clinical examination, hematological and biochemical analyses, ultrasonographic imaging of the liver, and histopathological assessment of liver tissue samples.ResultsAffected camels exhibited clinical indicators of chronic illness, including leukocytosis, neutrophilia, anemia, elevated alkaline phosphatase levels, and hyperglobulinemia. Ultrasonographic findings included increased hepatic echogenicity, nodular parenchymal patterns, indistinct hepatic vasculature, and the presence of peritoneal effusion. Histopathological examination revealed portal and bridging fibrosis, biliary hyperplasia, hepatocellular atrophy, Kupffer cell hyperplasia, and inflammatory infiltration. Parasitic structures were identified in some liver samples, suggesting a possible etiological factor.DiscussionThe study provides the first detailed, multimodal diagnostic profile of hepatic fibrosis in dromedary camels. The combination of clinical signs, laboratory abnormalities, imaging features, and histopathological findings supports the utility of an integrated diagnostic approach. The identification of parasitic structures in some cases warrants further investigation into potential infectious etiologies.